Novel multi-device unified powerquality conditioner for powerquality improvement - Naarisetti Srinivasa Rao; Pulipaka Venugopal Ramana Rao (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper describes the customizable multi-device unified power-quality conditioner (MD-UPQC) is designed especially for multi-feeder distribution networks. The proposed MD-UPQC can exchange the power between the multi-feeders and proficiently mitigates all voltage-current associated power-quality problems, make sure to maintain balanced power-flow to consumers. At recent days, various manufacturers recommend the provision of multilevel inverters in mid-range customized compensation devices with desirable control schemes. In distinct, the 5-level diode-clamped multi-level inverter (DCMLI) is best suited for MD-UPQC over traditional 3-level voltage source inverter (VSI) topology for attaining enhanced features. In this paper, MD-UPQC has been proposed with three 5-level DCMLI modules interfaced as back-to-back with a common direct current (DC) capacitor. The simplified phase-dispositional modulation technique is easily assembled with proposed universal voltage-current reference controller for significant functioning of DCMLI-MDUPQC device. The operation and performance of proposed model and its control scheme is evaluated with MATLAB/Simulink computational tool, simulation results are presented.